Preparation method of Na-doped SnSe thermoelectric thin film for improving orientation
Through non-in-situ doping and pulsed laser deposition technology, the preparation of Na-doped SnSe thermoelectric film is achieved, solving the problem of doping difficulties caused by Na element volatility, significantly optimizing the thermoelectric performance of the film, and having good application prospects.
Patent Information
- Application Number
- CN202510313315.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-29
AI Technical Summary
During the preparation of SnSe films, Na elements are very easy to volatilize and difficult to dopate in situ, making it difficult to achieve thermoelectric performance optimization.
Using non-in-situ doping preparation technology and pulsed laser deposition technology, a high-oriented SnSe thermoelectric film is first prepared, and then placed in a Na atmosphere for annealing to achieve Na doping.
A high-oriented Na-doped SnSe thermoelectric film was prepared, which greatly optimized its power factor and had excellent thermoelectric properties, and was suitable for thermoelectric micro-nano devices.
Smart Images

Figure CN119900004A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermoelectric functional film materials, and in particular to a method for preparing an orientation-enhanced Na-doped SnSe thermoelectric film. Background Art
[0002] Thermoelectric materials are functional materials that can directly convert heat and electrical energy. They can be used in waste heat / waste heat recovery power generation, refrigeration and temperature control, sensor detection and other fields. Thermoelectric devices prepared based on thermoelectric functional thin film materials have the advantages of being thin and light, easy to integrate on a large scale, high output power density, and fast response speed. They have important application prospects in the fields of self-powered wearable electronic devices, rapid refrigeration and precise temperature control of micro-nano chips.
[0003] In recent years, tin selenide (SnSe) is a newly discovered high-performance thermoelectric material that has attracted much attention due to its low cost of constituent elements and its green environmental protection. Intrinsic SnSe is a p-type semiconductor with inherent defects such as low carrier concentration and poor electrical properties.
[0004] In the prior art, the optimization of the thermoelectric performance of P-type SnSe bulk materials is mainly achieved by doping monovalent elements such as Na at the cation position to optimize its carrier concentration and improve its thermoelectric power factor. However, in the SnSe thin film preparation process, it is difficult to perform in-situ doping because the Na element is extremely volatile.
[0005] Therefore, there is an urgent need for a non-in-situ doping preparation technology for SnSe thin films with sodium to solve the above problems. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a Na-doped SnSe thermoelectric film with improved orientation. The method adopts non-in-situ doping preparation technology and pulsed laser deposition technology. The process is simple and a highly oriented Na-doped SnSe thermoelectric film is prepared. The power factor is greatly optimized and the film has excellent thermoelectric performance. The film has application prospects in thermoelectric micro-nano devices.
[0007] To achieve the above object, the present invention provides a method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation, comprising the following steps:
[0008] S1. Preparation of SnSe thermoelectric thin film using pulsed laser deposition technology;
[0009] S2, encapsulating the sodium source and the SnSe thermoelectric film obtained in S1 in a quartz tube using vacuum sealing technology;
[0010] S3. Put the quartz tube obtained in S2 into an annealing furnace for post-annealing treatment to obtain a Na-doped SnSe thermoelectric thin film.
[0011] Preferably, S1 is specifically:
[0012] S11, according to the proportion, high-purity tin powder and high-purity selenium powder are encapsulated in a quartz tube by using a vacuum tube sealing technology, and then placed in a muffle furnace for smelting into an ingot and grinding into powder, and finally pressure sintering is performed by using a spark plasma sintering technology to obtain a selenium-rich tin selenide polycrystalline target;
[0013] S12, a tin selenide polycrystalline target and an ultrasonically cleaned single crystal substrate are placed in a PLD cavity, and a tin selenide thermoelectric film is grown on the single crystal substrate by pulsed laser deposition technology to obtain a SnSe thermoelectric film.
[0014] Preferably, in S11, the atomic molar stoichiometric ratio of the high-purity tin powder to the high-purity selenium powder is Sn:Se=1:1.10-1.30.
[0015] Preferably, in S12, the single crystal substrate adopts a MgO-001 single crystal substrate.
[0016] Preferably, in S12, the controlled deposition conditions of the pulsed laser deposition technology are specifically:
[0017] The laser frequency is 3-5 Hz, and the laser density is 1.2-3.0 J / cm 2 , the argon pressure is 0.05-0.50 Pa, the base temperature of the single crystal substrate is 300-370° C., and the distance between the single crystal substrate and the tin selenide polycrystalline target is 4.0-6.0 cm.
[0018] Preferably, S2 is specifically:
[0019] S21, ultrasonically cleaning and drying the quartz tube using deionized water and 98% alcohol respectively;
[0020] S22. Encapsulate the SnSe thermoelectric film and the sodium source obtained in S1 in a quartz tube in proportion.
[0021] Preferably, in S22, the pressure in the quartz tube is 4×10 -5 Pa~4×10 -3 Pa.
[0022] Preferably, in S22, the sodium source is one or both of sodium fluoride and sodium chloride, and the mass ratio of the sodium source to the SnSe film is ≥10.
[0023] Preferably, S3 is specifically:
[0024] The packaged quartz tube is placed in an annealing furnace, and the temperature is raised from room temperature to 275°C to 350°C over 10 minutes to 1 hour at a constant heating rate, and maintained for 30 minutes to 2 hours. Finally, it is naturally cooled to room temperature to obtain a Na-doped SnSe thermoelectric thin film.
[0025] Therefore, the present invention adopts the above-mentioned method for preparing Na-doped SnSe thermoelectric thin film with improved orientation, and the beneficial effects are as follows:
[0026] The present invention adopts non-in-situ doping preparation technology and pulsed laser deposition technology, that is, firstly, pulsed laser deposition technology is adopted to prepare a highly oriented SnSe thermoelectric film, and then the SnSe thermoelectric film is annealed in a Na atmosphere environment, and the process is simple; a highly oriented Na-doped SnSe thermoelectric film is prepared, and its power factor is greatly optimized, and it has excellent thermoelectric performance, and has application prospects in thermoelectric micro-nano devices.
[0027] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is an XRD spectrum of an embodiment of a method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to the present invention;
[0029] Figure 2 It is a graph of the variation of the Seebeck coefficient (S) with the temperature (T) of an embodiment of a method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to the present invention;
[0030] Figure 3 It is a graph of the change of conductivity (σ) with temperature (T) of an embodiment of a method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to the present invention;
[0031] Figure 4 The graph is a graph showing the variation of power factor (PF) with temperature (T) in an embodiment of a method for preparing a Na-doped SnSe thermoelectric film with improved orientation according to the present invention. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0033] Unless otherwise defined, the technical terms or scientific terms used in the present invention shall have the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The experimental methods used in the present invention are all conventional methods unless otherwise specified, and the reagents and materials used can be obtained from commercial channels unless otherwise specified.
[0034] Example 1
[0035] A method for preparing an orientation-enhanced Na-doped SnSe thermoelectric thin film comprises the following steps:
[0036] S1. Prepare SnSe thermoelectric thin films using pulsed laser deposition technology.
[0037] High-purity tin powder and high-purity selenium powder weighed at an atomic molar ratio of Sn:Se=1:1.20 are packaged in a quartz tube using vacuum sealing technology, then placed in a muffle furnace to be melted into ingots and ground into powder, and finally pressure-sintered using spark plasma sintering technology to obtain a selenium-rich tin selenide polycrystalline target.
[0038] The tin selenide polycrystalline target and the single crystal substrate after ultrasonic cleaning are placed in the PLD cavity. In this embodiment, the single crystal substrate is a MgO-001 single crystal substrate. The tin selenide thermoelectric film is grown on the MgO-001 single crystal substrate by pulsed laser deposition technology. The deposition conditions are controlled to be a laser frequency of 5 Hz and a laser density of 1.5 J / cm 2 , the back pressure is 2×10 -4 Pa, the argon pressure is 0.1 Pa, the substrate temperature of the MgO-001 single crystal substrate is 350°C, and the distance between the MgO-001 single crystal substrate and the tin selenide polycrystalline target is 5.0 cm.
[0039] S2. The sodium source and the SnSe thermoelectric film obtained in S1 are encapsulated in a quartz tube using vacuum sealing technology.
[0040] The quartz tube was ultrasonically cleaned with deionized water and 98% alcohol for 5 times respectively. The cleaned quartz tube was placed in a constant temperature drying oven at a drying temperature of 70°C and a drying time of 20 hours.
[0041] The SnSe thermoelectric film obtained in S1 and 0.5 g of sodium fluoride particles (purity of 99.99%) were packaged together in a quartz tube with a diameter of 10 mm. The pressure inside the quartz tube was 8×10 -4 Pa, the volume of the packaged quartz tube is 7 mL.
[0042] S3, placing the quartz tube obtained in S2 into an annealing furnace for post-annealing treatment.
[0043] The packaged quartz tube was placed in an annealing furnace, and the temperature was raised from room temperature to 310°C in 20 minutes, and maintained for 30 minutes, and finally cooled naturally to room temperature, thus obtaining a highly oriented Na-doped SnSe thermoelectric film.
[0044] Example 2
[0045] A method for preparing an orientation-enhanced Na-doped SnSe thermoelectric thin film comprises the following steps:
[0046] S1. Prepare SnSe thermoelectric thin films using pulsed laser deposition technology.
[0047] High-purity tin powder and high-purity selenium powder weighed at an atomic molar ratio of Sn:Se=1:1.15 are packaged in a quartz tube using vacuum sealing technology, then placed in a muffle furnace to be melted into ingots and ground into powder, and finally pressure-sintered using spark plasma sintering technology to obtain a selenium-rich tin selenide polycrystalline target.
[0048] The tin selenide polycrystalline target and the single crystal substrate after ultrasonic cleaning are placed in the PLD cavity. In this embodiment, the single crystal substrate is a MgO-001 single crystal substrate. The tin selenide thermoelectric film is grown on the MgO-001 single crystal substrate by pulsed laser deposition technology. The deposition conditions are controlled to be a laser frequency of 5 Hz and a laser density of 1.5 J / cm 2 , the back pressure is 1×10 -4 Pa, the argon pressure is 0.1 Pa, the substrate temperature of the MgO-001 single crystal substrate is 330°C, and the distance between the MgO-001 single crystal substrate and the tin selenide polycrystalline target is 5.0 cm.
[0049] S2. The sodium source and the SnSe thermoelectric film obtained in S1 are encapsulated in a quartz tube using vacuum sealing technology.
[0050] The quartz tube was ultrasonically cleaned with deionized water and 98% alcohol for 5 times respectively. The cleaned quartz tube was placed in a constant temperature drying oven at a drying temperature of 70°C and a drying time of 20 hours.
[0051] The SnSe thermoelectric film obtained in S1 and 0.8 g of sodium fluoride particles (purity of 99.99%) were packaged together in a quartz tube with a diameter of 15 mm. The pressure inside the quartz tube was 3×10 -4 Pa, the volume of the packaged quartz tube is 10 mL.
[0052] S3, placing the quartz tube obtained in S2 into an annealing furnace for post-annealing treatment.
[0053] The packaged quartz tube is placed in an annealing furnace, and the temperature is raised from room temperature to 300°C in 30 minutes, and maintained for 30 minutes, and finally cooled naturally to room temperature, thus obtaining a highly oriented Na-doped SnSe thermoelectric film.
[0054] Example 3
[0055] A method for preparing an orientation-enhanced Na-doped SnSe thermoelectric thin film comprises the following steps:
[0056] S1. Prepare SnSe thermoelectric thin films using pulsed laser deposition technology.
[0057] High-purity tin powder and high-purity selenium powder weighed at an atomic molar ratio of Sn:Se=1:1.17 are packaged in a quartz tube using vacuum sealing technology, then placed in a muffle furnace to be melted into ingots and ground into powder, and finally pressure-sintered using spark plasma sintering technology to obtain a selenium-rich tin selenide polycrystalline target.
[0058] The tin selenide polycrystalline target and the single crystal substrate after ultrasonic cleaning are placed in the PLD cavity. In this embodiment, the single crystal substrate is a MgO-001 single crystal substrate. The tin selenide thermoelectric film is grown on the MgO-001 single crystal substrate by pulsed laser deposition technology. The deposition conditions are controlled to be a laser frequency of 5 Hz and a laser density of 1.6 J / cm 2 , the back pressure is 4×10 -4 Pa, the argon pressure is 0.1 Pa, the substrate temperature of the MgO-001 single crystal substrate is 360°C, and the distance between the MgO-001 single crystal substrate and the tin selenide polycrystalline target is 5.5 cm.
[0059] S2. The sodium source and the SnSe thermoelectric film obtained in S1 are encapsulated in a quartz tube using vacuum sealing technology.
[0060] The quartz tube was ultrasonically cleaned with deionized water and 98% alcohol for 5 times respectively. The cleaned quartz tube was placed in a constant temperature drying oven at a drying temperature of 70°C and a drying time of 20 hours.
[0061] The SnSe thermoelectric film obtained in S1 and 1.0 g of sodium fluoride particles (purity of 99.99%) were packaged together in a quartz tube with a diameter of 12 mm. The pressure inside the quartz tube was 7×10 -4 Pa, the volume of the packaged quartz tube is 8 mL.
[0062] S3, placing the quartz tube obtained in S2 into an annealing furnace for post-annealing treatment.
[0063] The packaged quartz tube was placed in an annealing furnace, and the temperature was raised from room temperature to 330°C in 40 minutes, and maintained for 60 minutes, and finally cooled naturally to room temperature, thus obtaining a highly oriented Na-doped SnSe thermoelectric film.
[0064] Comparative Example 1
[0065] A method for preparing a SnSe thermoelectric thin film comprises the following steps:
[0066] S1. Prepare SnSe thermoelectric thin films using pulsed laser deposition technology.
[0067] High-purity tin powder and high-purity selenium powder weighed at an atomic molar ratio of Sn:Se=1:1.22 are packaged in a quartz tube using vacuum sealing technology, then placed in a muffle furnace to be melted into ingots and ground into powder, and finally pressure-sintered using spark plasma sintering technology to obtain a selenium-rich tin selenide polycrystalline target.
[0068] The tin selenide polycrystalline target and the single crystal substrate after ultrasonic cleaning are placed in the PLD cavity. In this embodiment, the single crystal substrate is a MgO-001 single crystal substrate. The tin selenide thermoelectric film is grown on the MgO-001 single crystal substrate by pulsed laser deposition technology. The deposition conditions are controlled to be a laser frequency of 5 Hz and a laser density of 1.4 J / cm 2 , the back pressure is 3×10 -4 Pa, the argon pressure is 0.1 Pa, the substrate temperature of the MgO-001 single crystal substrate is 300°C, and the distance between the MgO-001 single crystal substrate and the tin selenide polycrystalline target is 4.5 cm.
[0069] S2, cooling naturally to room temperature, and obtaining a highly oriented SnSe thermoelectric film.
[0070] Experimental Testing
[0071] The highly oriented Na-doped SnSe thermoelectric films prepared in Examples 1-3 and the highly oriented SnSe thermoelectric films prepared in Comparative Example 1 were respectively subjected to XRD test analysis. The analysis results are as follows: Figure 1 shown.
[0072] Depend on Figure 1 It can be seen that the films prepared in Examples 1-3 are all highly oriented Na-doped SnSe thermoelectric films, and the film prepared in Comparative Example 1 is a highly oriented SnSe thermoelectric film.
[0073] The Seebeck coefficient test was carried out using the thermoelectric films prepared in Examples 1-3 and Comparative Example 1. The test results are as follows: Figure 2 shown.
[0074] Depend on Figure 2 It can be seen that the highly oriented Na-doped SnSe thermoelectric film prepared in Example 1 shows a Seebeck coefficient of about 352 μV / K at 600K, the highly oriented Na-doped SnSe thermoelectric film prepared in Example 2 shows a Seebeck coefficient of about 373 μV / K at 600K, the highly oriented Na-doped SnSe thermoelectric film prepared in Example 3 shows a Seebeck coefficient of about 423 μV / K at 600K, and the highly oriented SnSe thermoelectric film prepared in Comparative Example 1 shows a Seebeck coefficient of about 385 μV / K at 600K. This indicates that the incorporation of sodium into the film reduces the Seebeck coefficient.
[0075] The conductivity of the thermoelectric films prepared in Examples 1-3 and Comparative Example 1 was tested respectively. The test results are shown in Figure 3 .
[0076] Depend on Figure 3 It can be seen that the highly oriented Na-doped SnSe thermoelectric film prepared in Example 1 shows an electrical conductivity of about 3941 S / m at 600 K, the highly oriented Na-doped SnSe thermoelectric film prepared in Example 2 shows an electrical conductivity of about 4053 S / m at 600 K, the highly oriented Na-doped SnSe thermoelectric film prepared in Example 3 shows an electrical conductivity of about 3030 S / m at 600 K, and the highly oriented SnSe thermoelectric film prepared in Comparative Example 1 shows an electrical conductivity of about 3051 S / m at 600 K. This indicates that the incorporation of sodium into the film increases the electrical conductivity.
[0077] The power factors of the thermoelectric films prepared in Examples 1-3 and Comparative Example 1 were calculated based on the conductivity test and the Seebeck coefficient test results. Figure 4 .
[0078] Depend on Figure 4 It can be seen that the highly oriented Na-doped SnSe thermoelectric film prepared in Example 1 shows a power factor of about 4.9 μW / cm·K at 600K. 2 The highly oriented Na-doped SnSe thermoelectric film prepared in Example 2 shows a power factor of about 5.6 μW / cm·K at 600 K. 2 The highly oriented Na-doped SnSe thermoelectric film prepared in Example 3 shows a power factor of about 5.4 μW / cm·K at 600 K. 2 The highly oriented SnSe thermoelectric film prepared in Comparative Example 1 shows a power factor of about 4.5 μW / cm·K at 600 K. 2 .
[0079] This indicates that the addition of sodium into the film increases the conductivity and decreases the Seebeck coefficient, ultimately significantly optimizing the power factor to 0.3-0.9μW / cm·K 2 , a Na-doped SnSe thermoelectric film with excellent thermoelectric properties was obtained, which has application prospects in thermoelectric micro-nano devices.
[0080] Therefore, the present invention adopts the above-mentioned method for preparing the Na-doped SnSe thermoelectric film with improved orientation, adopts non-in-situ doping preparation technology and pulsed laser deposition technology, has a simple process, and can prepare a highly oriented Na-doped SnSe thermoelectric film, which greatly optimizes its power factor and has excellent thermoelectric properties, and has application prospects in thermoelectric micro-nano devices.
[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an orientation-enhanced Na-doped SnSe thermoelectric thin film, characterized in that: The following steps are involved: S1. Preparation of SnSe thermoelectric thin film using pulsed laser deposition technology; S2, encapsulating the sodium source and the SnSe thermoelectric film obtained in S1 in a quartz tube using vacuum sealing technology; S3. Put the quartz tube obtained in S2 into an annealing furnace for post-annealing treatment to obtain a Na-doped SnSe thermoelectric thin film.
2. The method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to claim 1, characterized in that: S1 is specifically: S11, according to the proportion, high-purity tin powder and high-purity selenium powder are encapsulated in a quartz tube by using a vacuum tube sealing technology, and then placed in a muffle furnace for smelting into an ingot and grinding into powder, and finally pressure sintering is performed by using a spark plasma sintering technology to obtain a selenium-rich tin selenide polycrystalline target; S12, a tin selenide polycrystalline target and an ultrasonically cleaned single crystal substrate are placed in a PLD cavity, and a tin selenide thermoelectric film is grown on the single crystal substrate by pulsed laser deposition technology to obtain a SnSe thermoelectric film.
3. The method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to claim 2, characterized in that: In S11, the atomic molar stoichiometric ratio of the high-purity tin powder to the high-purity selenium powder is Sn:Se=1:1.10-1.
30.
4. The method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to claim 2, characterized in that: In S12, the single crystal substrate adopts a MgO-001 single crystal substrate.
5. The method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to claim 2, characterized in that: In S12, the controlled deposition conditions of the pulsed laser deposition technology are specifically: The laser frequency is 3-5 Hz, and the laser density is 1.2-3.0 J / cm 2 , the argon pressure is 0.05-0.50 Pa, the base temperature of the single crystal substrate is 300-370° C., and the distance between the single crystal substrate and the tin selenide polycrystalline target is 4.0-6.0 cm.
6. The method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to claim 1, characterized in that: S2 is specifically: S21, ultrasonically cleaning and drying the quartz tube using deionized water and 98% alcohol respectively; S22. Encapsulate the SnSe thermoelectric film and the sodium source obtained in S1 in a quartz tube in proportion.
7. The method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to claim 6, characterized in that: In S22, the pressure inside the quartz tube is 4×10 -5 Pa~4×10 -3 Pa.
8. The method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to claim 6, characterized in that: In S22, the sodium source is one or both of sodium fluoride and sodium chloride, and the mass ratio of the sodium source to the SnSe film is ≥10.
9. The method for preparing a Na-doped SnSe thermoelectric thin film with improved orientation according to claim 1, characterized in that: S3 is specifically: The packaged quartz tube is placed in an annealing furnace, and the temperature is raised from room temperature to 275°C to 350°C over 10 minutes to 1 hour at a constant heating rate, and maintained for 30 minutes to 2 hours. Finally, it is naturally cooled to room temperature to obtain a Na-doped SnSe thermoelectric thin film.